Transgenerational Defense Priming for Crop Protection against Plant Pathogens: A Hypothesis - Ramírez-Carrasco, Gabriela; Martínez-Aguilar, Keren; Alvarez-Venegas, Raúl (Frontiers in Plant Science, 2017)
Throughout evolution, plants have developed diverse mechanisms of defense that “prime” their innate immune system for more robust and active induction of defense responses against different types of stress. Nowadays there are numerous reports concerning the molecular bases of priming, as well as the generational priming mechanisms. Information concerning transgenerational priming, however, remains deficient. Some reports have indicated, nonetheless, that the priming status of a plant can be inherited to its offspring. Here, we show that the priming agent β-aminobutyric acid induced resistance to Pseudomonas syringae pv. phaseolicola infection in the common bean (Phaseolus vulgaris L.) We have analyzed the transgenerational patterns of gene expression of the PvPR1 gene (Phaseolus vulgaris PR1), a highly responsive gene to priming, and show that a transgenerational priming response against pathogen attack can last for at least two generations. We hypothesize that a defense-resistant phenotype and easily identifiable, generational and transgenerational, “primed patterns” of gene expression are excellent indicators of the priming response in crop plants. Furthermore, we propose here that modern plant breeding methods and crop improvement efforts must include the use of elicitors to prime induced resistance in the field and, above all, to select for induced heritable states in progeny that is primed for defense.